Correcting Systemic Deficiencies in our Scientific Infrastructure - Mohan Doss (SAGE Publishing, 2014)
Scientific method is inherently self-correcting. When different hypotheses are proposed, their study would result in the rejection of the invalid ones. If the study of a competing hypothesis is prevented because of the faith in an unverified one, scientific progress is stalled. This has happened in the study of low dose radiation. Though radiation hormesis was hypothesized to reduce cancers in 1980, it could not be studied in humans because of the faith in the unverified linear no-threshold model hypothesis, likely resulting in over 15 million preventable cancer deaths worldwide during the past two decades, since evidence has accumulated supporting the validity of the phenomenon of radiation hormesis. Since our society has been guided by scientific advisory committees that ostensibly follow the scientific method, the long duration of such large casualties is indicative of systemic deficiencies in the infrastructure that has evolved in our society for the application of science. Some of these deficiencies have been identified in a few elements of the scientific infrastructure, and remedial steps suggested. Identifying and correcting such deficiencies may prevent similar tolls in the future.